2022
DOI: 10.1371/journal.pone.0267728
|View full text |Cite
|
Sign up to set email alerts
|

First case of successful eradication of the sweet potato weevil, Cylas formicarius (Fabricius), using the sterile insect technique

Abstract: This paper presents the first case of the successful eradication of a Coleoptera pest species over a wide area using a combination of male annihilation technique (MAT) and sterile insect technique (SIT) application. The sweet potato weevil, Cylas formicarius, is one of the most destructive and widely distributed pests of sweet potato, Ipomoea batatas. A project to eradicate it was launched in 1994 on Kume Island, Okinawa Prefecture, Japan. The MAT application was first used from November 1994 to January 1999 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Rapid development of sweet potato weevil and scab disease have caused heavy damage to the sweet potato production of many countries [8] [18]. However, it is difficult for farmers to accurately identify their outbreak, further supported by high number of pesticides indiscriminately, causing insect resistance and resurgence as well as serious environmental pollution [19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…Rapid development of sweet potato weevil and scab disease have caused heavy damage to the sweet potato production of many countries [8] [18]. However, it is difficult for farmers to accurately identify their outbreak, further supported by high number of pesticides indiscriminately, causing insect resistance and resurgence as well as serious environmental pollution [19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have also reported that sex pheromone‐baited plastic pole traps caught 60%–78% more weevils than sex pheromone‐baited delta traps, wing traps, or unitraps (Dilipkumar et al., 2019). Successful eradication of these weevils has been reported using a combination of male annihilation techniques and sterile insect technique in Kume Island, Japan (Himuro et al., 2022). Use of male annihilation techniques reduced the wild population density in a few years, followed by the release of millions of sterile weevils, which helped to completely eradicate the weevils from Kume Island.…”
Section: Pest and Disease Management In Sweetpotato Productionmentioning
confidence: 99%
“…The female sex pheromone of the sweetpotato weevil has been identified, synthesized, and used for their control (Heath et al, 1986; Chalfant et al, 1990; Yasuda, 1995; Kohama & Haraguchi, 2010; Himuro et al, 2022). This pheromone obtained from virgin females strongly attracts only males in the field and laboratory and elicits an overt series of behaviors (activation, orientation, and sexual movements).…”
Section: Introductionmentioning
confidence: 99%